Kinetic analysis of pelvis horizontal rotation of angled instep kicking in soccer - Inoue, K.; Nunome, H. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Previous study illustrated that matured instep kick included appreciable pelvis counter-clockwise rotation and that motion was induced by torques mainly due to ground reaction force (Inoue et al., 2014). However, mechanical factors that induce the pelvis rotation have not been revealed when players kick the ball to varied angles. This study aimed, therefore, to clarify the kinetic aspects of the pelvis rotation when players kick the ball towards angled directions. Methods: Nine male soccer players performed maximum instep kicks towards three angled directions (15, 45 and 75 deg.). Their motions and ground reaction forces were recorded by a motion capture system at 500 Hz. Angular velocity and torque vectors regarding the support leg and the pelvis were calculated, and then the components that induce the pelvis rotation on the horizontal plane were extracted. Results: An increase of the angle of kicking direction led to a significant (p<0.05) increase of the range of the pelvis rotation. With increasing the kicking angle, the higher hip joint torques of the support leg were observed. The angular impulses due to the hip joint torques were systematically and significantly (p<0.05) increased with an increase of kicking direction angle. The ranges of foot segment rotation (ROM) of the support leg were also systematically emphasized with an increase of the kicking direction angle while the torques for the foot rotation were small to be negligible in all the kicking directions. Discussion: Scurr & Hall (2009) reported that soccer players displayed a greater pelvic rotation when using a wider approach angle. Levanon & Dapena (1998) argued that the pelvic rotation has a role to face the anterior half of the thigh (kicking leg side) onto the target direction. In this study, we succeeded in illustrating how the kinetic background changes when players kick the ball to angled directions. Inoue et al. (2014) already demonstrated that the interaction torque due to ground reaction force is the main drive in producing the pelvis rotation in normal straight instep kicking. We accumulated additional knowledge about the emphasized pelvis rotation when the ball was kicked to angled directions. The pelvis rotation was emphasized in response to the increased kicking angles. The hip joint torque (angular impulse) of the support leg was the kinetic factor systematically corresponded to the change of kicking directions. Thus, it can be assumed that the hip joint torque of the support leg is responsible for the increased pelvic rotations. Likewise, we observed the foot rotation was increased with an increase of the kicking angles. However, this motion was not accompanied by the action of the torque. Hence, it is most likely that the foot rotation is passively induced by some other factors such as partial friction of the floor acting on the foot segment.